2015
DOI: 10.1007/s12035-015-9385-x
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound

Abstract: Traumatic brain injury (TBI) is a leading cause of death and disability in the USA. Effective therapeutic strategies for TBI are needed, and increasing attention is turning toward traditional herbal medicine. Rhizoma drynariae is a traditional Chinese medicine that has immunomodulatory and anti-inflammatory effects. Here, using the controlled cortical impact model of TBI in rats, we examined whether oral administration of R. drynariae can reduce TBI-induced brain injury in rats. We also identified the likely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 46 publications
0
52
0
Order By: Relevance
“…Cognitive functions were evaluated with the Morris water maze (MWM) test as described previously (Vorhees and Williams 2006; Wang et al 2015). Briefly, a rat was placed in a large circular pool (130 cm in diameter and 60 cm high) filled with warm (19–22 °C) water to a depth of 30 cm.…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive functions were evaluated with the Morris water maze (MWM) test as described previously (Vorhees and Williams 2006; Wang et al 2015). Briefly, a rat was placed in a large circular pool (130 cm in diameter and 60 cm high) filled with warm (19–22 °C) water to a depth of 30 cm.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a promising therapeutic strategy used for neurodegenerative diseases was focused on blocking microglial activation processes (Kim and Joh, 2006;Yuan et al, 2016). Recently, numerous studies have reported that traditional Chinese medicine exert neuroprotective effects through suppressing microglial activation, and their effects have been elevated to have the potential to treat neurodegenerative diseases Wang et al, 2016). Our present study demonstrated that salidroside, a central bioactive constituent of the traditional Chinese herb Rhodiola, significantly inhibits LPS-induced inflammation in microglial cells, and provided an underlying mechanism for the neuroprotective effects of Sal in microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Rhodiola is a widely used TCM herb that has been shown to improve cognitive function, reduce mental fatigue, decrease free radicals, and enhance learning and memory (Darbinyan et al, 2000;Shevtsov et al, 2003). Salidroside (Sal) is the major phenylpropanoid glycoside extract from Rhodiola and has various bioactive effects, including anti-inflammatory, neuroprotective (Qu et al, 2012;Sun et al, 2012), attenuation of bleomycin-induced pulmonary fibrosis (Tang et al, 2016) and attenuation of arthritis-induced brain cognitive deficits (Zhu et al, 2016). Moreover, Sal could down-regulate NF-κB signaling pathways to prevent fibrosis and brain cognitive deficits (Tang et al, 2016;Zhu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbal medicine plays a significant role in drug discovery and development11. Neuroscientists and doctors hope that novel chemical entities derived from herbal medicines could improve TBI treatment and reduce the risk of mortality and disability12.…”
mentioning
confidence: 99%